IDENTIFICATION OF DYSFUNCTIONAL MODULES WITHIN A PHOTOVOLTAIC GENERATOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This research paper presents the design and the realization of a system that can detect dysfunctions in modules constituting a photovoltaic generator, the proposed system is intended to monitor an autonomous photovoltaic generator and to discern which photovoltaic module is out of order based on the use of its characteristics such as the by-pass diode and the output voltage. This method can also be used to gain time while searching the dysfunction in the system with the auto-diagnostic algorithm, and it makes the maintenance work faster and easier than conventional, which reduces the photovoltaic power loss. The results show that through simple algorithmic calculation and divider bridges, we can know the state of the photovoltaic generator and which module is dysfunctional and then display the result to the user.
Keywords: Photovoltaic module; By-pass diode; Photovoltaic power; Divider bridges